Women's narratives on learning through migration - Kožar Rosulnik, Klara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2016)
The article focuses on the migration experiences of women as a source for research into learning. The theoretical framework for the phenomenological research comprises biographical and transitional learning, i.e., biographical learning that takes place at life transitions. This kind of learning is considered as a process that occurs during experiences in everyday life that involve the reconstruction of identity, knowledge, skills, attitudes and values. Transitional learning theory is used because migrations represent important life passages that are complex heterogeneous experiences, creating possibilities for learning which are experienced in various ways by different individuals. The research is empirical, being based on the analysis of selected narratives of women who have immigrated to or emigrated from Slovenia. From the narrations themes are inductively designed that define learning as a cumulative process. The analysis of each thematic section identifies the strategies of learning and the types of knowledge involved. On the basis of these findings, a model for interpreting migration-related biographical learning is formed.
Keywords: human migration; migracije; biografsko učenje; avtobiografska metoda; woman; ženske; pripovedi